Associations of Genetically Determined Continental Ancestry With CD4+ Count and Plasma HIV-1 RNA Beyond Self-Reported Race and Ethnicity. (15th April 2016) - Brummel, Sean S.; Singh, Kumud K.; Maihofer, Adam X.; Farhad, Mona; Qin, Min; Fenton, Terry; Nievergelt, Caroline M.; Spector, Stephen A.
Abstract : Background: Ancestry informative markers (AIMs) measure genetic admixtures within an individual beyond self-reported racial/ethnic (SRR) groups. Here, we used genetically determined ancestry (GDA) across SRR groups and examine associations between GDA and HIV-1 RNA and CD4 + counts in HIV-positive children in the United States. Methods: Forty-one AIMs, developed to distinguish 7 continental regions, were detected by real-time PCR in 994 HIV-positive, antiretroviral naive children. GDA was estimated comparing each individual's genotypes to allele frequencies found in a large set of reference individuals originating from global populations using STRUCTURE. The means of GDA were calculated for each category of SRR. Linear regression was used to model GDA on CD4 + count and log10 RNA, adjusting for SRR and age. Results: Subjects were 61% black, 25% Hispanic, 13% white, and 1.3% Unknown. The mean age was 2.3 years (45% male), mean CD4 + count of 981 cells per cubic millimeter, and mean log10 RNA of 5.11. Marked heterogeneity was found for all SRR groups with high admixture for Hispanics. In adjusted linear regression models, subjects with 100% European ancestry were estimated to have 0.33 higher log10 RNA levels (95% CI: 0.03 to 0.62, P = 0.028) and 253 CD4 + cells per cubic millimeter lower (95% CI: −517 to 11, P = 0.06) in CD4 + count, compared to subjects with 100% African ancestry. Conclusion: Marked continental admixture was found among this cohort of HIV-infected children from the United States. GDA contributed to differences in RNA and CD4 + counts beyond SRR and should be considered when outcomes associated with HIV infection are likely to have a genetic component. Abstract : Supplemental Digital Content is Available in the Text.